Hardmetal and cutting tools
The carbide alloy, with its tailored microstructure and composition, addresses the challenge of machining high-hardness materials by extending tool life through improved wear and fatigue resistance.
Patent Information
- Application Number
- JP2024529596
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Cutting tools face increased difficulty in machining high-hardness materials, leading to reduced tool life and performance.
A carbide alloy comprising tungsten carbide particles and a bonding phase with a specific composition and microstructure, including a first region near the surface with a higher proportion of hcp cobalt and a second region deeper with a higher proportion of fcc cobalt, optimizing deformation resistance and strength.
The carbide alloy extends the tool life of cutting tools, particularly when used for intermittent machining of high-hardness materials, by enhancing wear resistance, fracture resistance, and fatigue strength.
Smart Images

Figure 0007666745000005 
Figure 0007666745000006 
Figure 0007666745000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to hardmetals and cutting tools. [Background technology]
[0002] Conventionally, cemented carbide having a plurality of tungsten carbide particles and a binder phase has been used as a material for cutting tools (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-131769 A Summary of the Invention
[0004] The cemented carbide of the present disclosure is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes a first region within 15 μm from the surface and a second region more than 15 μm from the surface; The area S1 of cobalt having an hcp structure in the binder phase of the first region (hcp) and the area S1 of cobalt having an fcc structure (fcc) The total of the area S1 (hcp) Ratio R1 and area S2 of cobalt having a hcp structure in the binder phase of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The sum of the above area S2 (hcp) The ratio R1 / R2 is 1.8 or less. [Brief description of the drawings]
[0005] [Figure 1] FIG. 1 is a schematic cross-sectional view of a cemented carbide according to a first embodiment. [Diagram 2] FIG. 2 is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] [Problem that this disclosure aims to solve] In recent years, work materials have become increasingly difficult to cut in cutting processes, and the conditions under which cutting tools are used have become harsher. For this reason, there is a demand for improved properties in the cemented carbide alloys used as the base material for cutting tools. In particular, there is a demand for cemented carbide alloys that can extend the tool life even when used as materials for cutting tools for interrupted cutting of high-hardness materials, and for cutting tools equipped with such cemented carbide alloys.
[0007] [Effects of this disclosure] According to the present disclosure, it is possible to provide a cemented carbide alloy and a cutting tool having the same that enable a longer tool life, particularly when used as a material for cutting tools for intermittent machining of high-hardness materials.
[0008] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The cemented carbide disclosed herein is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes a first region within 15 μm from the surface and a second region more than 15 μm from the surface; The area S1 of cobalt having an hcp structure in the binder phase of the first region (hcp) and the area S1 of cobalt having an fcc structure(fcc) The total of the area S1 (hcp) Ratio R1 and area S2 of cobalt having a hcp structure in the binder phase of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The sum of the above area S2 (hcp) The ratio R1 / R2 is 1.8 or less.
[0009] According to the present disclosure, it is possible to provide a cemented carbide that enables a longer tool life, particularly when used as a material for cutting tools for interrupted machining of high-hardness materials.
[0010] (2) In the above (1), the ratio R1 / R2 may be 1.2 or more and 1.5 or less, thereby improving the balance between the deformation resistance and strength of the binder phase of the cemented carbide, and allowing a cutting tool including the cemented carbide to have a longer tool life.
[0011] (3) In the above (1) or (2), the binder phase may further contain at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, thereby improving the balance between the deformation resistance and strength of the binder phase of the cemented carbide, and allowing a cutting tool including the cemented carbide to have a longer tool life.
[0012] (4) In the above (3), the percentage of the mass M1 of the first element to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, may be 1% or more and 6% or less. According to this, the binder phase can have both superior hardness and superior toughness, so that a cutting tool including a cemented carbide containing the binder phase can have a longer tool life.
[0013] (5) A cutting tool according to the present disclosure is a cutting tool having a cutting edge made of the cemented carbide according to any one of (1) to (4) above.
[0014] According to the present disclosure, it is possible to provide a cutting tool having a long tool life, especially when used for interrupted cutting of high hardness materials.
[0015] [Details of the embodiment of the present disclosure] Specific examples of the cemented carbide and cutting tool of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. Furthermore, dimensional relationships such as length, width, thickness, and depth have been appropriately changed for clarity and simplification of the drawings, and do not necessarily represent actual dimensional relationships.
[0016] In this disclosure, an expression in the form "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.
[0017] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, it is intended to include any conventionally known atomic ratio, and should not necessarily be limited to only those within the stoichiometric range.
[0018] In the present disclosure, when one or more numerical values are described as the lower limit and the upper limit of a numerical range, a combination of any one numerical value described as the lower limit and any one numerical value described as the upper limit is also disclosed. For example, when a1 or more, b1 or more, and c1 or more are described as the lower limit, and a2 or less, b2 or less, and c2 or less are described as the upper limit, a1 or more and a2 or less, a1 or more and b2 or less, a1 or more and c2 or less, b1 or more and a2 or less, b1 or more and b2 or less, b1 or more and c2 or less, c1 or more and a2 or less, c1 or more and b2 or less, and c1 or more and c2 or less are disclosed.
[0019] [Embodiment 1: Carbide] A cemented carbide according to one embodiment of the present disclosure will be described with reference to FIG. The cemented carbide 3 according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 1") is A cemented carbide (3) comprising a plurality of tungsten carbide particles (1) and a binder phase (2), The cemented carbide 3 contains tungsten carbide particles 1 and a binder phase 2 in a total amount of 89 volume % or more, The cemented carbide 3 contains a binder phase 2 in an amount of 1.8 volume % or more and 20 volume % or less, The binder phase 2 contains 80% by mass or more of cobalt, The cemented carbide 3 includes a first region within 15 μm from the surface and a second region more than 15 μm from the surface, Area S1 of cobalt having hcp structure in binder phase 2 of the first region (hcp) and the area S1 of cobalt having an fcc structure (fcc) The total area S1 (hcp) Ratio R1 and area S2 of cobalt having hcp structure in binder phase 2 of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) The ratio R1 / R2 of the ratio R1 to the ratio R2 is 1.8 or less.
[0020] The cemented carbide of the first embodiment can provide a cemented carbide that enables a tool to have a long life, even when used as a material for cutting tools for interrupted cutting of high-hardness materials, and a cutting tool including the same. The reason for this is not clear, but is presumed to be as follows.
[0021] The cemented carbide of the first embodiment comprises a plurality of tungsten carbide particles (hereinafter also referred to as "WC particles") and a binder phase, and the total content of the WC particles and the binder phase in the cemented carbide is 89 volume % or more. As a result, the cemented carbide has high hardness and strength, and a cutting tool comprising the cemented carbide can have excellent wear resistance and chipping resistance.
[0022] The cemented carbide of the first embodiment contains a binder phase of 1.8% by volume or more and 20% by volume or less, and the binder phase contains 80% by mass or more of cobalt. Thus, the cemented carbide has high hardness and strength, and a cutting tool including the cemented carbide can have excellent wear resistance and chipping resistance.
[0023] In the cemented carbide of embodiment 1, the area S1 of cobalt having an hcp structure in the binder phase of the first region (hcp) and the area S1 of cobalt having an fcc structure (fcc) The total area S1 (hcp) Ratio R1 and area S2 of cobalt having hcp structure in the binder phase of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) The ratio R1 / R2 between the ratio R2 and the ratio R1 is 1.8 or less. The first region on the surface side of the cemented carbide has a higher proportion of the hcp structure in the binder phase than the second region on the inner side of the cemented carbide, so that the deformation resistance of the binder phase on the surface side of the cemented carbide is improved. As a result, the cutting tool including the cemented carbide has improved plastic deformation resistance at the beginning of cutting. The second region on the inner side of the cemented carbide has a higher proportion of the fcc structure in the binder phase than the first region, so that the strength of the inner side of the cemented carbide is improved. As a result, the cutting tool including the cemented carbide can have excellent fatigue strength even when the inside of the cemented carbide is exposed during cutting. The cemented carbide of the first embodiment has an improved balance between the deformation resistance and strength of the binder phase, and the cutting tool including the cemented carbide has improved chipping resistance in high-load processing such as intermittent processing of high-hardness materials, and can have a long tool life.
[0024] <Composition of cemented carbide> The cemented carbide of the first embodiment contains tungsten carbide particles and a binder phase in a total amount of 89% or more by volume. This can increase the hardness of the cemented carbide. The cemented carbide may contain tungsten carbide particles and a binder phase in a total amount of 89% to 100% by volume, 90% to 100% by volume, 91% to 100% by volume, or 92% to 100% by volume.
[0025] The cemented carbide of the first embodiment contains 1.8% by volume or more and 20% by volume or less of a binder phase. This can increase the hardness and toughness of the cemented carbide. The content of the binder phase in the cemented carbide may be 2.0% by volume or more and 19.0% by volume or less, 3.0% by volume or more and 18.0% by volume or less, or 4.0% by volume or more and 17.0% by volume or less.
[0026] The cemented carbide of the first embodiment may be composed of a plurality of tungsten carbide particles and a binder phase. In this case, the cemented carbide may contain impurities within a range that does not impair the effects of the present disclosure.
[0027] The cemented carbide may contain other phases (not shown) in addition to the tungsten carbide particles and binder phase. The other phases may include carbides, nitrides, or carbonitrides containing at least one element selected from the group consisting of titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), hafnium (Hf), and molybdenum (Mo). The composition of the other phases may be, for example, at least one selected from the group consisting of TiCN, TaC, NbC, ZrC, HfC, Cr3C2, and Mo2C.
[0028] The cemented carbide of the first embodiment may be composed of tungsten carbide particles, a binder phase, and other phases. In this case, the cemented carbide may contain impurities as long as the effects of the present disclosure are not impaired.
[0029] The content of other phases in the cemented carbide is permitted within a range that does not impair the effects of the present disclosure. For example, the content of other phases in the cemented carbide may be 0 vol% or more and 11 vol% or less, more than 0 vol% and 11 vol% or less, more than 0 vol% and 7 vol% or less, or more than 0 vol% and 4 vol% or less.
[0030] The cemented carbide of the first embodiment may contain impurities. Examples of impurities include iron (Fe), calcium (Ca), silicon (Si), and sulfur (S). The content of impurities in the cemented carbide is permissible within a range that does not impair the effects of the present disclosure. For example, the content of impurities in the cemented carbide may be 0% by mass or more and less than 0.1% by mass. The content of impurities in the cemented carbide is measured by ICP optical emission spectroscopy (Inductively Coupled Plasma Emission Spectroscopy). The measurement device that can be used is Shimadzu Corporation's "ICPS-8100" (trademark).
[0031] The content of tungsten carbide particles in the cemented carbide of embodiment 1 may be 67 vol. % to 98.2 vol. %, 70 vol. % to 97 vol. %, or 75 vol. % to 96 vol. %.
[0032] The method for measuring the content (volume %) of tungsten carbide particles in the cemented carbide and the content (volume %) of the binder phase in the cemented carbide is as follows.
[0033] (A1) An arbitrary position of the cemented carbide is cut out to expose a cross section, which is then mirror-finished using a cross-section polisher (manufactured by JEOL Ltd.).
[0034] (B1) The mirror-finished surface of the cemented carbide is analyzed using an energy dispersive X-ray spectrometer (SEM-EDX) attached to a scanning electron microscope (equipment: Carl Zeiss "Gemini450" (trademark)) to identify the elements contained in the cemented carbide.
[0035] (C1) The mirror-finished surface of the cemented carbide is photographed with a scanning electron microscope (SEM) to obtain a backscattered electron image. The photographed area is set to the center of the cemented carbide cross section, that is, a position that does not include areas with properties that are clearly different from the bulk part, such as the surface area of the cemented carbide (a position where the entire imaged area is the bulk part of the cemented carbide). The observation magnification is 5000x. The measurement conditions are an acceleration voltage of 3kV, a current value of 2nA, and a working distance (WD) of 5mm.
[0036] (D1) The photographed region of (C1) above is analyzed using SEM-EDX to identify the distribution of the elements identified in (B1) above in the photographed region, and an element mapping image is obtained.
[0037] (E1) The backscattered electron image obtained in (C1) above is imported into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, tungsten carbide particles are shown in white, and the bond phase is shown in gray to black. Note that the binarization threshold changes depending on the contrast, so it is set for each image.
[0038] (F1) By superimposing the element mapping image obtained in (D1) above and the image after the binarization process obtained in (E1) above, the respective regions of the tungsten carbide particles and the binder phase are identified on the image after the binarization process. Specifically, the regions shown in white in the image after the binarization process and in which tungsten (W) and carbon (C) exist in the element mapping image correspond to the regions of the tungsten carbide particles. The regions shown in gray to black in the image after the binarization process and in which cobalt (Co) exists in the element mapping image correspond to the regions of the binder phase.
[0039] (G1) A rectangular measurement field of view of 24.9 μm × 18.8 μm is set in the image after the binarization process. Using the image analysis software, the area percentages of the tungsten carbide particles and the binder phase are measured with the area of the entire measurement field as the denominator.
[0040] (H1) The measurement of (G1) above is carried out in five different non-overlapping measurement fields. In the present disclosure, the average of the area percentages of tungsten carbide particles in the five measurement fields corresponds to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentages of the binder phase in the five measurement fields corresponds to the content (volume %) of the binder phase in the cemented carbide.
[0041] If the cemented carbide contains other phases in addition to the WC particles and the binder phase, the content of the other phases in the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binder phase measured by the above procedure from the total cemented carbide (100 volume %).
[0042] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described in (G1) above are arbitrarily set and the tungsten carbide particle content and binder phase content of the cemented carbide are measured multiple times according to the above procedure.
[0043] The cemented carbide of embodiment 1 may contain 1% or more by mass of cobalt. The cobalt content of the cemented carbide may be 1.0% or more and 20% or less by mass, 2.0% or more and 15% or less by mass, or 3.0% or more and 12% or less by mass.
[0044] The method for measuring the cobalt content of the cemented carbide is as follows. Analysis is performed using SEM-EDX in the same manner as (A1) to (D1) of the method for measuring the tungsten carbide particle content and the binder phase content of the cemented carbide to obtain an element mapping image. Based on the element mapping image, the cobalt region in the cemented carbide is identified, and the cobalt content is measured. The measurement is performed in five different non-overlapping imaging regions. In the present disclosure, the average of the cobalt contents in the five imaging regions corresponds to the cobalt content of the cemented carbide.
[0045] As long as the measurements were performed on the same sample, it was confirmed that there was almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide and the photographing area described in (C1) above were arbitrarily set and the cobalt content of the cemented carbide was measured multiple times according to the above procedure.
[0046] <Tungsten carbide particles> In the cemented carbide of the first embodiment, the tungsten carbide particles include at least one of "pure WC particles (including WC containing no impurity elements and WC containing impurity elements below the detection limit)" and "WC particles containing impurity elements intentionally or unavoidably, as long as the effect of the present disclosure is not impaired." The content of impurities in the tungsten carbide particles (when two or more elements are included as impurities, the total concentration of the elements) is less than 0.1% by mass. The content of impurities in the tungsten carbide particles is measured by ICP emission spectrometry.
[0047] In the first embodiment, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm or more and 3.5 μm or less. It has been confirmed that the cemented carbide of the first embodiment can extend the life of a cutting tool when used as a material for the cutting tool, regardless of the average particle size of the tungsten carbide particles.
[0048] <Binded phase> In the cemented carbide of embodiment 1, the binder phase contains 80% by mass or more of cobalt. This allows the cemented carbide to have excellent toughness. The cobalt content of the binder phase may be 80% by mass or more and 100% by mass or less, 80% by mass or more and less than 100% by mass, or 90% by mass or more and less than 100% by mass.
[0049] The method for measuring the cobalt content of the binder phase is as follows. An element mapping image and an image after binarization are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the image after binarization are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. The cobalt content is measured in the region in which the binder phase exists in the measurement field of view. The above measurement is performed in five different measurement fields that do not overlap each other. In the present disclosure, the average of the cobalt contents in the regions in which the binder phase exists in the five measurement fields of view corresponds to the cobalt content of the binder phase.
[0050] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described above are arbitrarily set and the cobalt content of the binder phase is measured multiple times according to the above procedure.
[0051] In the cemented carbide of embodiment 1, the binder phase may further contain at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, which improves the deformation resistance of the binder phase.
[0052] The inclusion of the first element in the binder phase is confirmed by the following procedure. An element mapping image and a binarized image are obtained by the same methods as (A1) to (E1) of the above-mentioned method for measuring the tungsten carbide particle content and binder phase content of a cemented carbide alloy. The element mapping image and the binarized image are superimposed to identify the region in the element mapping image where the binder phase exists. Element Mapping image When the first element is present in the region where the binder phase is present, it is confirmed that the binder phase contains the first element.
[0053] In the binder phase of the cemented carbide of the first embodiment, the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element with respect to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt may be 1% or more and 6% or less. Here, the units of M1 and M2 are the same. As a result, the binder phase can have both better hardness and better toughness, so that a cutting tool including a cemented carbide including the binder phase can have a longer tool life. Here, the mass M1 of the first element means the total mass of all the types of the first elements when the binder phase includes two or more types of the first elements. The percentage {M1 / (M1+M2)}×100 may be 2% or more and 5% or less, or 3% or more and 4% or less.
[0054] The method for measuring the percentage {M1 / (M1+M2)}×100 is as follows. An element mapping image and a binarized image are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the binarized image are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. In the region in which the binder phase exists in the measurement field of view, the percentage {m1 / (m1+m2)}×100 of the mass m1 of the first element relative to the sum m1+m2 of the mass m1 of the first element and the mass m2 of cobalt is calculated. The above measurement is performed in five different measurement fields of view that do not overlap each other. In the present disclosure, the average of the percentage {m1 / (m1+m2)}×100 in the five measurement fields corresponds to the "percentage {M1 / (M1+M2)}×100" in the binder phase of the cemented carbide.
[0055] As long as measurements were taken on the same sample, it was confirmed that there was almost no variation in the measurement results, even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view were arbitrarily set, and the percentage {M1 / (M1+M2)}×100 was measured multiple times according to the above procedure.
[0056] In the cemented carbide of the first embodiment, the binder phase may contain, in addition to cobalt and the first element, at least one second element selected from the group consisting of iron, nickel, and chromium. The binder phase may consist of cobalt, the first element, and the second element. The binder phase may consist of cobalt, the first element, the second element, and inevitable impurities. Examples of the inevitable impurities include iron, nickel, and sulfur.
[0057] <Ratio R1 / R2> The cemented carbide of embodiment 1 includes a first region within 15 μm from the surface and a second region more than 15 μm from the surface, and the area S1 of cobalt having a hcp (hexagonal close-packed) structure in the binder phase of the first region (hcp) and the area S1 of cobalt with fcc (face-centered cubic) structure (fcc) The total area S1 (hcp) Ratio R1 and area S2 of cobalt having hcp structure in the binder phase of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) The ratio R1 / R2 is 1.8 or less. (hcp) / (S1 (hcp) +S1 (fcc) ) and the ratio R2 is S2 (hcp) / (S2 (hcp) +S2 (fcc) ) Area S1 (hcp) , area S1 (fcc) , area S2 (hcp) and area S2 (fcc) The units are the same.
[0058] R1 / R2 may be 1.2 or more and 1.8 or less, 1.2 or more and 1.7 or less, 1.2 or more and 1.6 or less, 1.2 or more and 1.5 or less, 1.2 or more and 1.4 or less, or 1.2 or more and 1.3 or less.
[0059] R1 may be 0.5 or more and 1.0 or less, 0.6 or more and 0.9 or less, or 0.7 or more and 0.8 or less. When the ratio R1 is 0.5 or more and 1.0 or less, the plastic deformation resistance of the cutting tool at the initial stage of cutting is improved.
[0060] R2 may be 0.3 or more and 0.6 or less, 0.35 or more and 0.55 or less, or 0.4 or more and 0.5 or less. When the ratio R2 is 0.3 or more and 0.6 or less, the fatigue strength of the cutting tool is improved.
[0061] In the present disclosure, R1 / R2 is measured by the following procedure.
[0062] (A2) The cemented carbide is cut along the normal line of its main surface to expose a cross section. If the surface of the cemented carbide does not have a flat area, the cemented carbide is cut from an arbitrary point on the surface in a direction toward the center of gravity of the cemented carbide to expose a cross section. The cross section is mirror-finished using a cross section polisher (manufactured by JEOL Ltd.).
[0063] (B2) The mirror-finished surface of the cemented carbide is observed using a scanning electron microscope (SEM: Carl Zeiss "Gemini450" (trademark)) equipped with an electron backscatter diffraction device (EBSD device: Oxford "Symmetry" (trademark)). EBSD analysis is performed on the obtained observation image. The observation image is acquired so as to include a region sandwiched between the surface of the cemented carbide and a virtual plane that is 50 μm away from the surface to the inside of the cemented carbide. In the observation image, a first rectangular measurement field of view of 11.5 μm × 8.5 μm is set in a first region that is within a distance of 15 μm from the surface. In the observation image, a second rectangular measurement field of view of 11.5 μm × 8.5 μm is set in a second region that is more than 15 μm away from the surface. The observation magnification is 10,000 times. The measurement conditions are an acceleration voltage of 15 kV, a current value of 20 nA, 0.02 μm / step, an exposure time of 1.5 to 3 ms, and a measurement time of 10 to 20 minutes.
[0064] (C2) The above EBSD analysis results are analyzed using commercially available software (Oxford "AZtecCrystal" (trademark)), and the crystal structure of cobalt contained in the binder phase is identified in each of the first and second measurement fields of view, and a color map is obtained. The crystal structure of cobalt identified here is the crystal structure observed when the cobalt appearing on the mirror-finished surface of the cemented carbide is viewed in plan from the normal direction of the mirror-finished surface.
[0065] (D2) Using the above software, the area S of cobalt having the hcp structure in the bond phase of each of the first and second measurement fields is measured. (hcp) and the area S of cobalt with fcc structure (fcc) The total area S (hcp) For example, based on a color map, image A showing tungsten carbide particles in white and cobalt having an hcp structure in black and image B showing tungsten carbide particles in white and cobalt having an fcc structure in black are output, and the ratio R can be measured based on image A and image B.
[0066] (E2) The measurement of the ratio R is performed in three mutually non-overlapping first measurement fields and three mutually non-overlapping second measurement fields. In the present disclosure, the average of the ratios R in the three first measurement fields is determined to be the area S1 of cobalt having a hcp structure in the binder phase of the first region of the cemented carbide. (hcp) and the area S1 of cobalt having an fcc structure (fcc) The total area S1 (hcp) In the present disclosure, the average of the ratios R in the three second measurement fields corresponds to the area S2 of cobalt having a hcp structure in the binder phase of the second region of the cemented carbide. (hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) This corresponds to the ratio R2.
[0067] (F2) Calculate R1 / R2 based on the ratio R1 and the ratio R2 obtained in (E2) above.
[0068] As long as measurements were taken on the same sample, it was confirmed that there was almost no variation in the measurement results even if the cut-out location of the cemented carbide cross section, the area for obtaining the observation image described in (B2) above, and the measurement field of view were arbitrarily set and R1 / R2 was measured multiple times according to the above procedure.
[0069] <Method of manufacturing cemented carbide> The cemented carbide of the embodiment 1 can be manufactured by carrying out the steps of preparing raw material powder, mixing, molding, and sintering in the above-mentioned order. Each step will be described below.
[0070] <Preparation process> The preparation step is a step of preparing raw material powders of materials constituting the cemented carbide. Examples of the raw material powders include tungsten carbide powder (hereinafter also referred to as "WC powder"), cobalt (Co) powder, first element powder, and alloy powder of the first element and cobalt. Examples of the first element powders include silicon (Si) powder, phosphorus (P) powder, germanium (Ge) powder, tin (Sn) powder, rhenium (Re) powder, ruthenium (Ru) powder, osmium (Os) powder, iridium (Ir) powder, and platinum (Pt) powder. Examples of the raw material powders include nickel (Ni) powder, niobium carbide (NbC) powder, carbide (Cb) powder, and carbide (Cc) powder. tantalum (TaC) powder, titanium carbonitride (TiCN) powder, chromium carbide (Cr3C2) powder, etc. can be prepared. These raw material powders can be commercially available. The average particle size of these raw material powders is not particularly limited and can be, for example, 0.5 to 2 μm. The average particle size of the raw material powder means the average particle size measured by the FSSS (Fisher Sub-Sieve Sizer) method. The average particle size is measured using a "Sub-Sieve Sizer Model 95" (trademark) manufactured by Fisher Scientific.
[0071] <Mixing process> The mixing step is a step of mixing the raw material powders prepared in the preparation step in a predetermined ratio. A mixed powder in which the raw material powders are mixed is obtained by the mixing step. The mixing ratio of the raw material powders is appropriately adjusted depending on the composition of the target cemented carbide.
[0072] The raw material powders can be mixed by a conventionally known mixing method such as an attritor, a ball mill, or a bead mill. Conventional known conditions can also be used for the mixing conditions. The mixing time can be, for example, 2 hours or more and 20 hours or less.
[0073] After the mixing step, the mixed powder may be granulated as necessary. By granulating the mixed powder, it becomes easier to fill the mixed powder into a die or a mold during the molding step described below. For granulation, a known granulation method can be applied, and for example, a commercially available granulator such as a spray dryer can be used.
[0074] <Forming process> The molding step is a step of molding the mixed powder obtained in the mixing step into a shape for a cutting tool to obtain a molded body. The molding method and molding conditions in the molding step are not particularly limited and may be general methods and conditions.
[0075] <Sintering process> The sintering process is a process in which the compact obtained in the compacting process is sintered to obtain a cemented carbide intermediate. The sintering conditions are as follows: The compact is placed in a sintering furnace and held at 7 MPa and 1360°C for 2 hours.
[0076] <Cooling process> The cooling step is a step of cooling the cemented carbide intermediate body after the sintering step. Specifically, the cemented carbide intermediate body is released from the sintering furnace into the air and rapidly cooled to room temperature at a temperature drop rate of −100° C. / min to obtain the cemented carbide of the first embodiment.
[0077] <Features of the method for producing the cemented carbide according to the first embodiment> In the method for producing a cemented carbide according to the first embodiment, the sintering step is performed by holding the cemented carbide intermediate body under conditions of 7 MPa and 1360°C for 2 hours. In the cooling step, rapid cooling is performed at a temperature drop rate of -100°C / min. This cooling rate is higher than conventional cooling rates. Under these conditions, the area S1 of cobalt having a hcp structure in the binder phase of the first region of the cemented carbide is increased. (hcp) and the area S1 of cobalt having an fcc structure (fcc) The total area S1 (hcp) Ratio R1 and area S2 of cobalt having hcp structure in the binder phase of the second region (hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) In the present invention, the ratio R1 / R2 of R1 to R2 of R2 is 1.8 or less. The present inventors have found, through extensive investigations, that the cemented carbide of the present disclosure can be realized by employing such a sintering step and a cooling step.
[0078] [Embodiment 2: Cutting tool] A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 2") includes a cutting edge made of the cemented carbide of embodiment 1. In this disclosure, the cutting edge refers to a portion involved in cutting. More specifically, the cutting edge refers to a region surrounded by a cutting edge ridge and an imaginary surface that is 0.5 mm or 2 mm away from the cutting edge ridge toward the cemented carbide side.
[0079] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting tips for milling, indexable cutting tips for turning, metal saws, gear cutting tools, reamers, taps, etc. As shown in Fig. 2, the cutting tool 10 of the second embodiment can exhibit excellent effects, particularly in the case of an end mill. The cutting edge 11 of the cutting tool 10 shown in Fig. 2 is made of the cemented carbide of the first embodiment.
[0080] In the cutting tool of the second embodiment, the cemented carbide of the first embodiment may constitute the whole of these tools or may constitute a part of them. Here, "constitute a part" refers to a mode in which the cemented carbide of the first embodiment is brazed to a predetermined position of any substrate to form a cutting edge.
[0081] The cutting tool of the second embodiment may further include a hard film that covers at least a part of the surface of the substrate made of cemented carbide. The hard film may be made of, for example, diamond-like carbon or diamond.
[0082] The cutting tool of the second embodiment can be obtained by forming the cemented carbide of the first embodiment into a desired shape. EXAMPLES
[0083] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.
[0084] [Preparation of cemented carbide] Each sample of cemented carbide was prepared according to the following procedure. <Preparation process> As the raw material powders, WC powder (average particle size: 1 μm), Co powder (average particle size: 1 μm), first element powder, TiCN powder (average particle size: 1 μm), Ni powder (average particle size: 1 μm) were prepared. As the first element powders, silicon (Si) powder (average particle size: 1 μm), phosphorus (P) powder (average particle size: 1 μm), germanium (Ge) powder (average particle size: 1 μm), tin (Sn) powder (average particle size: 1 μm), rhenium (Re) powder (average particle size: 1 μm), ruthenium (Ru) powder (average particle size: 1 μm), osmium (Os) powder (average particle size: 1 μm), iridium (Ir) powder (average particle size: 1 μm), and platinum (Pt) powder (average particle size: 1 μm) were prepared.
[0085] <Mixing process> A mixed powder was obtained by mixing the raw material powders for 10 hours using an attritor in the ratios shown in Table 1. The ratio (mass%) of each raw material powder shown in Table 1 is the ratio when the entire mixed powder is taken as 100 mass%.
[0086] [Table 1]
[0087] <Forming process> The mixed powder was pressed to obtain a rod-shaped compact.
[0088] <Sintering process> The compact was placed in a sintering furnace and held at the pressure and temperature shown in the "Holding pressure" and "Holding temperature" columns of the "Sintering process" in Table 2 for the time shown in the "Holding time" column. This resulted in a cemented carbide intermediate. The "vac" in the "Holding pressure" column means in a vacuum.
[0089] <Cooling process> The cemented carbide intermediate body after the sintering step was released from the sintering furnace into the atmosphere and cooled at the temperature decreasing rate shown in the "Temperature decreasing rate" column of "Cooling step" in Table 2, to obtain each sample of cemented carbide.
[0090] [Table 2]
[0091] [Evaluation of cemented carbide] <Content (volume %) of tungsten carbide particles and binder phase (volume %) of cemented carbide> The content (volume %) of tungsten carbide particles and the content (volume %) of the binder phase of the cemented carbide of each sample were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "WC particle content" and "binder phase content" columns of "Cemented carbide" in Table 3. Furthermore, the total content of tungsten carbide particles and the binder phase of the cemented carbide are shown in the "WC particle + binder phase content" column of "Cemented carbide" in Table 3. In Table 3, it was confirmed that the cemented carbide with the "WC particle + binder phase content" column of less than 100 volume % further contained TiCN.
[0092] [Table 3]
[0093] <Cobalt content in binder phase> The cobalt content of the binder phase of each sample of cemented carbide was measured. The specific measurement method is as described in embodiment 1. The results are shown in the "Co content" column of "Binder phase" in Table 4.
[0094] <{M1 / (M1+M2)}×100> In the binder phase of the cemented carbide of each sample, the type of the first element and the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element relative to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "First element" and "{M1 / (M1+M2)}×100" columns of "Binder phase" in Table 4. The samples marked with "-" in the "First element" column do not contain the first element.
[0095] <Ratio R1 / R2> In each sample of cemented carbide, the area S1 of cobalt having a hcp (hexagonal close-packed) structure in the binder phase in the first region within a distance of 15 μm from the surface (hcp) and the area S1 of cobalt with fcc (face-centered cubic) structure (fcc) The total area S1 (hcp) Ratio R1 and area S2 of cobalt having hcp structure in the binder phase in the second region at a distance of more than 15 μm from the surface(hcp) and the area S2 of cobalt with fcc structure (fcc) The total area S2 (hcp) The ratio R1 / R2 of R1 to the ratio R2 of R1 was measured. The specific measurement method is as described in embodiment 1. R1, R2 and the ratio R1 / R2 are shown in the "R1", "R2" and "R1 / R2" columns of "bonded phase" in Table 4.
[0096] [Cutting test] A round bar made of cemented carbide of each sample was machined to prepare a ball end mill with a blade diameter of φ3 mm. The ball end mill was used to perform intermittent side cutting of a workpiece made of SDK61 (with holes of φ2 mm at equal intervals). The cutting conditions were cutting speed Vc 100 m / min, feed per blade fz 0.05 mm / blade, cutting depth (axial direction) ap 0.05 mm, cutting depth (radial direction) ae 0.05 mm, dry. The cutting length until chipping occurred on the cutting tool was measured. The longer the cutting length, the longer the tool life. The results are shown in the "Cutting length" column of "Cutting test" in Table 4. The above processing conditions correspond to intermittent cutting of high hardness materials.
[0097] [Table 4]
[0098] [Consideration] The cemented carbide and cutting tools of Samples 1 to 19 correspond to Examples. The cemented carbide and cutting tools of Samples 101 to 106 correspond to Comparative Examples. It was confirmed that the cutting tools of Samples 1 to 19 had longer tool life than the cutting tools of Samples 101 to 106.
[0099] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways. The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]
[0100] 1 Tungsten carbide particles, 2 binder phase, 3 cemented carbide, 10 cutting tool, 11 cutting edge.
Claims
1. A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes a first region within 15 μm from the surface and a second region more than 15 μm from the surface; The area S1 of cobalt having an hcp structure in the binder phase of the first region (hcp) and the area S1 of cobalt having an fcc structure (fcc) The area S1 with respect to the sum of (hcp) and the area S2 of cobalt having a hcp structure in the binder phase of the second region. (hcp) and the area S2 of cobalt having an fcc structure (fcc) The area S2 with respect to the sum of (hcp) The ratio R1 / R2 is 1.2 or more and 1.8 or less, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; In the binder phase, a percentage of the mass M1 of the first element relative to a sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, is 1% or more and 6% or less; The cemented carbide, wherein R2 is 0.32 or more.
2. 2. The cemented carbide according to claim 1, wherein the ratio R1 / R2 is equal to or greater than 1.2 and equal to or less than 1.
5.
3. A cutting tool having a cutting edge made of the cemented carbide according to claim 1 or 2.
Citation Information
Patent Citations
Cutting tool made of diamond-coated cemented carbide excellent in toughness and wear resistance
JP2013111711A
Cutting tool having excellent deposition chipping resistance
JP2019063932A
Surface-coated cutting tool excellent in deposition chipping resistance
JP2019063937A
Cemented carbide tool
JP2022079855A
Folding length adjustment device
KR1020230126422A